Prevalence of and risk factors for diabetic retinopathy in residents with different types of abnormal glucose metabolism with or without hypertension: A suburban community-based cross-sectional study - Ma, Yuhang; Wang, Hao; Jiang, Junyi; Han, Changjing; Lu, Chunhua; Zeng, Siliang; Wang, Yufan; Zheng, Zhi; Peng, Yongde; Ding, Xiaoying (Frontiers in Endocrinology, 2022)
Aims The present study examined the prevalence and risk factors for diabetic retinopathy (DR) in residents with abnormal glucose metabolism in a community. Methods 6029 subjects were included and underwent standardized interviews and comprehensive examinations. Residents with diabetes were divided into nondiabetic retinopathy (NDR) and DR groups and non-hypertension and hypertension groups. Unconditional multivariate logistic regression models were used to analyze the risk factors for DR in different groups. Results The prevalence of DR in diabetes was 9.9%, and the prevalence of retinopathy, which also has the typical signs of DRs, such as retinal microaneurysms, in prediabetes and normal glucose tolerance was 5.2% and 5.3%, respectively. An elevated waist-to-hip ratio (WHR) (female≥0.85, male≥0.9)[OR 1.683, 95% CI (1.016, 2.790)], systolic blood pressure (SBP)≥140 mmHg [OR 1.875, 95% CI (1.158, 3.034)], elevated HbA1c [OR 1.410, 95% CI (1.220, 1.629)], HbA1c ≥6.5% [OR 2.149, 95% CI (1.320, 3.498)], antidiabetic drug use [OR 3.798, 95% CI (2.209, 6.529)], elevated fasting blood glucose [OR 1.176, 95% CI (1.072, 1.289)], elevated postprandial blood glucose [OR 1.090, 95% CI (1.033, 1.150)] and nonspecific ST-T segment changes on electrocardiography [OR 2.555, 95% CI (1.556, 4.196)] were risk factors for DR. Duration of diabetes [OR 1.206, 95% CI (1.028, 1.415)], elevated WHR [OR 3.796, 95% CI (1.144, 12.603)], elevated waist circumference [OR 6.874, 95% CI (1.403, 33.665)], elevated HbA1c [OR 1.435, 95% CI (1.046, 1.970)], HbA1c ≥6.5% [OR 6.850, 95% CI (1.771, 26.501)], and concurrent metabolic syndrome [OR 3.975, 95% CI (1.144, 13.815)] were risk factors for DR in diabetes without hypertension, and elevated HbA1c [OR 1.395, 95% CI (1.183, 1.645)], HbA1c ≥6.5% [OR 1.745, 95% CI (1.027, 2.966)], use of antidiabetic drugs [OR 4.781, 95% CI (2.624, 8.711)], elevated fasting blood glucose [OR 1.146, 95% CI (1.034, 1.270)], elevated postprandial blood glucose [OR 1.083, 95% CI (1.020, 1.151)], and nonspecific ST-T segment changes on electrocardiography [OR 2.616, 95% CI (1.531, 4.469)] were risk factors for DR in diabetes with hypertension. Conclusion Retinopathy was found in subjects with normal glucose tolerance and prediabetes. There were differences in risk factors for DR in diabetic patients with and without hypertension.